A Fertile Ambiguity: The Case of Art Criticism - Tayac, Sébastien (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2023)
Whether approaching dawn or twilight, current art criticism is in a phase of profound change, generating many questions about its multidisciplinary essence. By confronting past and present Western writings about art criticism from philosophers, art historians, art sociologists, and artists from the 18th to the 21st century, this article gives a general overview of the various definitions of art criticism for students or lecturers unfamiliar with the subject. By examining the discrepancies and similarities between different theories, the aim of this article is to compare the various historical origins of art criticism and to highlight questions concerning the philosophy and methodology of art critics, so that we may examine the present and future relevance of art criticism in the art world.